A case of aplasia cutis congenita following fetal reduction of triplet pregnancy conceived through in vitro fertilization - Kim, Sae Yun; Kim, Eun Sun; Min, Joonhong; Lee, Kyungyul (The Turkish Journal of Pediatrics, 2022)
Background. Aplasia cutis congenita (ACC) is a rare congenital localized skin defect that is mostly diagnosed in the newborn or infant period. ACC type 5 often involves the trunk or extremities accompanied by fetus papyraceous (FP) or placental infarcts. The etiology and pathogenesis of this rare type of ACC are not well known. In this case, we report an ACC type 5 with a definite etiology. Case. We report a preterm infant with ACC type 5, with diffuse bilateral leg lesions found at birth. He was the first baby of dichorionic twin after reduction from a dichorionic triplet pregnancy conceived through in vitro fertilization. A fetus papyraceous was found in juxtaposition with the affected baby`s placenta. After 37 days of hospitalization, his leg lesions were successfully epithelized with supportive care. He is regularly visiting the Dermatology clinic for scar care and shows normal development without motor limitation. Conclusions. Herein, we present a preterm infant with ACC type 5 and the placental pathology with fetus papyraceous of the artificially reduced monochorionic co-twin of the affected infant. We suggest a precautious decision in multifetal pregnancy reduction (MFPR) in dichorionic triplets, presenting ACC type 5 as an adverse outcome of MFPR.
Keywords: aplasia cutis congenita; fetus papyraceous; in vitro fertilization; multifetal pregnancy reduction